Living with the enemy : inside North Korea - Saccone, Richard (Elizabeth, N.J. : Hollym International Corp., 2006)
Describes the author's travel experiences and cultural observations while working for the Korean Peninsula Energy Development Organization (KEDO) as a U.S. representative to build a nuclear power plant for the North Koreans. After living there on and off for almost fourteen years, Saccone seeks "to recognize Inaccurate portrayals of North Korea and reveal the truth."
Published simultaneously in Seoul, Korea.
Keywords: Korean Peninsula Energy Development Organization; Americans -- Korea (North); Nuclear facilities -- Korea (North); Korea (North) -- Politics and government; Korea (North) -- Description and travel; Korea (North) -- Social life and customs; United States -- Foreign relations -- Korea (North); Korea (North) -- Foreign relations -- United States